The effective factors on disclosure of intellectual capital in listed companies in Tehran stock exchange - Bita Mashaykhi; Seyyed Jalal Seyyedi; Hasti Zargaran Yazd (بررسی‌های حسابداری و حسابرسی, 2014)
Intellectual capital (IC) is one of the most precious assets of companies. In accounting literature a huge amount of attention has been paid to IC and its effects but disclosure of IC is a missing topic in the accounting studies. This paper tries to fill this gap and create a proper area for creation and development of IC. In this paper, the influential factors on disclosure of IC have been studied. For this purpose 63 companies (189 year–company), between period of 2010-2012, are investigated and the result shows a significant positive relationship between growth opportunity and age of company with IC disclosure, however, for profitability and financial leverage the result is in the opposite side. According to IC components, human capital disclosure has a significant negative relation with profitability, growth opportunity and age of company. Customer capital disclosure and structural capital have significant positive relations with growth opportunity and age of company, however, this result is not the same for financial leverage.